2013
DOI: 10.1007/s10840-013-9792-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hemodynamics and proinflammatory cytokines during biatrial and right atrial appendage pacing in patients with interatrial block

Abstract: PurposeInteratrial block (IAB) frequently coexists with sinus node disease and is considered a risk factor of left atrial dysfunction, atrial arrhythmias, and heart failure development. Conventional right atrial appendage (RAA) pacing impairs intra- and interatrial conductions and consequently prolongs P wave duration. Biatrial (BiA) pacing helps correct IAB, but its advantageous influence remains controversial. The aim of the study was to compare the effects of BiA and RAA pacing on cardiac hemodynamics and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Barani et al (11) examined inflammatory factors in patients with critical limb ischemia and found a significantly higher serum NPT levels in those with AF than in patients in sinus rhythm. Rubaj et al (37) reported a significant decrease in NPT levels at 1 week of biatrial pacing in comparison to right atrial appendage pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Barani et al (11) examined inflammatory factors in patients with critical limb ischemia and found a significantly higher serum NPT levels in those with AF than in patients in sinus rhythm. Rubaj et al (37) reported a significant decrease in NPT levels at 1 week of biatrial pacing in comparison to right atrial appendage pacing.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Rubaj et al, the authors sought to determine whether biatrial pacing improves cardiac hemodynamic function and reduces serum concentrations of inflammatory mediators in patients with IAB [43]. Twenty-eight patients with IAB and preserved AV conduction were evaluated under both BiA and RAA pacing.…”
Section: Biatrial Pacing In Iabmentioning
confidence: 99%
“…Importantly, it has been suggested that NPs including TiO 2 NPs can be translocated to heart, cause myocardial dysfunction, oxidative stress, cardiac inflammation and atherosclerosis in mice, induce plaque progression in aorta of mice, endothelial inflammatory response in primary vascular endothelial cells, and cardiac infarction in rats . As known, cardiac inflammation adversely affects cardiopulmonary hemodynamics in animals and human . Hemodynamics is a hydrodynamic problem for studying the flow of blood in the cardiovascular system, its basic research object is the relationship between flow resistance and pressure, and studies the effect of drugs on the cardiac function of the organism, pharmacological effects, and mechanisms of cardiovascular drugs.…”
Section: Introductionmentioning
confidence: 99%